136 Challenges in providing emergency response during COVID-19 at coastal areas of Bangladesh. (20th November 2022) - Hossen, Md Kabir; Dutta, Notan Chandra; Talab, Abu; Ahmed, Farukh; Rahman, Aminur
Abstract : Background: First aid is an emergency response to a victim for injury before the provision of medical treatment to prevent worsening of the victim's condition. During the COVID-19, first-aider faced challenges to provide the emergency response to the victims. Aim: To explore the challenges to providing an emergency response by community first aid volunteers among the victims. Method: A total of 2842 first-aid volunteers served among 2, 81, 000 populations under a drowning prevention project. In-depth interviews were conducted with first aid master trainers, first-aid responders, and service recipients, where thematic and content analysis was performed. In addition, injury event data were analyzed for 2-years periods of time, before and during the COVID-19 pandemic. Result: Only 10.3% got an emergency response during COVID-19 compared to prior normal situations. Volunteers followed the proper preventive mechanism of COVID-19 during first-aid service as and when required. In the normal situation from 2018–19 received services by 3283 persons whereas, during the pandemic, only 336 persons received first-aid service. So at least 2947 people did not get an emergency response during the pandemic. 89.7% of those were supposed to receive the emergency response they deteriorated and worsened the injury and increased further damage resulting in more suffering and economic cost. Conclusion: Due to COVID-19, the possibility of life risk becomes high due to emergency response limits. The preventive mechanism works to some extent. Learning outcomes: An adaptive mechanism can be developed to provide service during pandemics.